Distillery Yeast Sludge (DYS) as an Alternative Feed Resource in Poultry - Rameshwari, K. Sudha; Karthikeyan, S. (International Journal of Poultry Science, 2005)
With India`s livestock population approaching 100 million, the demand for dry fodder and concentrates is more than twice the supply and the demand for green fodder is four times the supply mean while 242 MT sugarcane is produced annually with lot of yeast sludge awaiting disposal. Hence, the present investigation was aimed at determining the nutritive content of distillery yeast sludge (DYS) and its use as a value added feed additive. It was fed to white leghorn chicks of one week of age for a period of 45 days at different levels of incorporation (0%, 10%, 30%, 50%, 70%). One bird of each treatment died except in the control and the 10% level. The marginal decline in weight gain was observed with increasing levels of DYS in the diet. At the end of 45th day of experiment, blood was collected from the surviving birds and biochemically analyzes the Hemoglobin, serum protein, calcium and phosphorus The cost of feed per 100g live weight gain decreased with the inclusion of DYS in the diet than in the control feed. The results thus indicate that DYS, after washing, can safely be included for growing chick, up to 30% level with distinct economic advantages.